Strategic Narratives : communication power and the new world order - Miskimmon, Alister; O'Loughlin, Ben, 1976-; Roselle, Laura (New York : Routledge, 2013)
"Communication is central to how we understand international affairs. Political leaders, diplomats, and citizens recognize that communication shapes global politics. This has only been amplified in a new media environment characterized by Internet access to information, social media, and the transformation of who can communicate and how. Soft power, public diplomacy 2.0, network power - scholars and policymakers are concerned with understanding what is happening. This book is the first to develop a systematic framework to understand how political actors seek to shape order through narrative projection in this new environment. To explain the changing world order - the rise of the BRICS, the dilemmas of climate change, poverty and terrorism, the intractability of conflict - the authors explore how actors form and project narratives and how third parties interpret and interact with these narratives. The concept of strategic narrative draws together the most salient of international relations concepts, including the links between power and ideas; international and domestic; and state and non-state actors. The book is anchored around four themes: order, actors, uncertainty, and contestation. Through these, Strategic Narratives shows both the possibilities and the limits of communication and power, and makes an important contribution to theorizing and studying empirically contemporary international relations"--
Includes bibliographical references and indexes.
Keywords: Communication in politics; Mass media; Social media; International relations; Social policy; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / Public Policy / General